Electrolyte and lithium battery containing same

By using a combination of lithium salt, silicone compound and haloalkane-based inducer in the lithium battery electrolyte, the problem of insufficient stability and antioxidant performance between the high-voltage positive electrode and the lithium metal negative electrode is solved, and the long cycle life and high Coulomb efficiency of the battery are achieved.

CN119864501AActive Publication Date: 2025-04-22BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD

Patent Information

Application Number
CN202311369952.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22
Estimated Expiration
2043-10-20

AI Technical Summary

Technical Problem

The existing lithium battery electrolyte has problems with insufficient stability and oxidation resistance between the high-voltage positive electrode and the lithium metal negative electrode, resulting in battery capacity attenuation and safety risks.

Method used

An electrolyte system containing lithium salt, siloxane compounds and halogenated alkane-based inducer is adopted to improve the solubility of lithium salt and the antioxidant properties of the electrolyte through the intermolecular interaction between the silicone compound and the inducer.

Benefits of technology

The electrolyte has good stability for both high-voltage positive electrode and lithium metal negative electrode, expands the electrochemical window, and improves the cycle life and Coulomb efficiency of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864501A_ABST
    Figure CN119864501A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and a lithium battery containing the same. The electrolyte comprises a lithium salt, a solvent and an inducer, the solvent comprises one or more of siloxane compounds as shown in a formula I; the inducer is selected from one or more of C1-C5 halogenated alkanes, C1-C5 halogenated cycloalkanes, C2-C6 halogenated aliphatic ethers and C6-C12 halogenated aromatic compounds. The electrolyte provided by the invention utilizes the intermolecular interaction force between the siloxane compound and the inducer, so that the dissolution of the lithium salt in the solvent is realized, and the electrolyte has high compatibility to a lithium metal negative electrode, has a wide electrochemical window, can be well matched with a high-voltage positive electrode material and a lithium metal negative electrode material, and has a good application prospect. And the cycle life and coulombic efficiency of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to an electrolyte and a lithium battery containing the electrolyte. Background Art

[0002] Lithium secondary batteries have become one of the research hotspots in the current energy storage field due to their high energy density and cycle performance. The performance improvement of lithium-ion batteries based on the traditional lithium cobalt oxide, graphite negative electrode and commercial electrolyte framework is about to reach the upper limit and can no longer keep up with the growing demand of consumers.

[0003] Lithium metal has an extremely low standard potential and density. When used as a negative electrode, it can greatly improve the energy density of lithium secondary batteries. Therefore, it is one of the candidate negative electrode materials for preparing high energy density lithium batteries. However, lithium metal has high reactivity and is prone to continuous side reactions with traditional carbonate-based electrolytes, resulting in the continuous thickening of the solid electrolyte film (SEI) on the negative electrode surface. The impedance continues to increase with the cycle, causing the battery capacity to decay; moreover, lithium ions tend to be unevenly deposited on the negative electrode surface, resulting in the growth of lithium dendrites, causing battery short circuits, and even fire and explosion. Therefore, it is crucial to design a new electrolyte system to replace traditional carbonate-based electrolytes and improve the safety of lithium metal batteries.

[0004] As one of the important components of the battery, the lithium battery electrolyte is generally composed of lithium salts, solvents and additives, which together determine the performance of the electrolyte. Among them, the key issues of lithium metal battery electrolytes are: 1) whether it has stability to the lithium metal negative electrode, and 2) whether it has good antioxidant stability to the positive electrode side. Although the electrolyte based on ethylene glycol dimethyl ether system, which is widely reported at present, has good compatibility with the negative electrode side and its coulombic efficiency (CE) can reach more than 99%, its oxidation stability on the positive electrode side is poor (<4V), and it is difficult to be applied to lithium metal batteries based on high-voltage positive electrode materials such as lithium nickel cobalt manganese oxide, lithium nickel manganese oxide and lithium cobalt oxide. High-concentration electrolytes (containing high-concentration lithium salts) or local high-concentration electrolytes (containing high-concentration lithium salts and fluoroether diluents) can improve the antioxidant capacity of solvent molecules on the positive electrode side to a certain extent due to the reduction in the number of free solvents, but a large amount of lithium salts are required and the price of fluoroether diluents is high, which undoubtedly increases the manufacturing cost of the electrolyte.

[0005] Therefore, designing and developing a new electrolyte with a wide electrochemical window that takes into account both the high-voltage stability on the positive electrode side and the stable performance on the lithium metal negative electrode side is of great significance for promoting the rapid development of high-energy-density lithium metal batteries. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide an electrolyte and a lithium battery containing the same. The electrolyte has good stability to both high-voltage positive electrodes and lithium metal negative electrodes, has a wide electrochemical window, can be well matched with high-voltage positive electrode materials and lithium metal negative electrode materials, can be used in high-energy-density lithium metal batteries, and helps to improve the cycle life and coulombic efficiency of the battery.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an electrolyte, the electrolyte comprising: a lithium salt, a solvent and an inducer;

[0009] The solvent includes one or more of the siloxane compounds shown in Formula I;

[0010]

[0011] wherein X1 and X2 are each independently selected from one of C1-C4 (e.g. C1, C2, C3, C4) alkyl groups, and R is selected from one of *-OLO-*; or, X1 and X2 are each independently selected from one of C1-C4 (e.g. C1, C2, C3, C4) alkoxy groups, and R is selected from one of C2-C4 (e.g. C2, C3, C4) alkylene groups and *-OLO-*;

[0012] L is selected from C2-C4 (e.g. C2, C3, C4) alkylene, *-Y1-O-Y2-*, Y1 and Y2 are each independently selected from one of C1-C2 alkylene groups, and Y3 is selected from one of C1-C3 (e.g., C1, C2, C3) alkylene groups;

[0013] -* represents the attachment site of the group;

[0014] The inducing agent is selected from one or more of C1-C5 (e.g. C1, C2, C3, C4, C5) halogenated alkanes, C1-C5 (e.g. C1, C2, C3, C4, C5) halogenated cycloalkanes, C2-C6 (e.g. C2, C3, C4, C5, C6) halogenated fatty ethers and C6-C12 (e.g. C6, C7, C8, C9, C10, C11, C12) halogenated aromatic compounds.

[0015] In the electrolyte provided by the present invention, the inducer can change the molecular configuration of the siloxane compound shown in formula I, so that the electronegativity of the O atom increases sharply, and the intermolecular interaction between the two is utilized to realize the dissolution of the lithium salt in the solvent. Among them, due to the strong bond energy force between Si-O and the hyperconjugated interaction, the siloxane compound has fewer side reactions on the positive electrode side and higher antioxidant performance; at the same time, due to the strong anti-reduction ability of the siloxane compound and the weak solvation ability generated by the intermolecular mutual force between the siloxane compound and the inducer, a SEI film rich in LiF components generated by the decomposition of anions will be generated on the negative electrode side, which can well block the further reaction of the solvent with the lithium metal negative electrode. Therefore, the electrolyte provided by the present invention has good stability for both high-voltage positive electrode materials and lithium metal negative electrode materials, and can improve the long cycle life and coulomb efficiency of lithium batteries.

[0016] In some embodiments of the present invention, the molar ratio of the siloxane compound to the inducer is 1:(2-6); for example, it can be 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5 or 1:6, etc.

[0017] In the present invention, when the molar ratio of the siloxane compound to the inducer is maintained within the above range, the siloxane compound has good solubility in the lithium salt. If the molar ratio of the siloxane compound to the inducer is too large or too small, the solubility in the lithium salt will be poor.

[0018] In some embodiments of the present invention, the siloxane compound is selected from one or more of 1,2-bis(trimethylsiloxy)ethane, 1,3-bis(trimethylsiloxy)propane, 1,2-bis(tert-butyldimethylsiloxy)ethane, bis[2-(trimethylsiloxy)ethyl]ether, 1,2-bis(dimethylethoxysilyl)ethane, trimethylsilanol trisilyloxyglycolate and 2,3-bis(trimethylsiloxy)-1,3-butadiene, preferably 1,2-bis(trimethylsiloxy)ethane and / or 1,3-bis(trimethylsiloxy)propane.

[0019] In some embodiments of the present invention, the halogen substituent in the C1-C5 halogenated alkane, C1-C5 halogenated cycloalkane, C2-C6 halogenated aliphatic ether and C6-C12 halogenated aromatic compound is fluorine and / or chlorine.

[0020] Since the inducing effect of the inducing agent containing bromine and iodine substituents on the siloxane compound is worse than that of fluorine and chlorine substituents, and the high pressure resistance is not good, the above-mentioned halogen substituents in the present invention are preferably fluorine and / or chlorine.

[0021] In some embodiments of the present invention, the C1-C5 halogenated alkane is selected from one or more of chloroform, dichloromethane, 1,2-dichloroethane, 1,3-dichloropropane, 1,1,2,2-tetrachloroethane, 2,2-dichloro-1,1,1-trifluoroethane and pentafluorobutane.

[0022] In some embodiments of the present invention, the C1-C5 halogenated cycloalkane is heptafluorocyclopentane.

[0023] In some embodiments of the present invention, the C2-C6 halogenated fatty ether is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and / or 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether.

[0024] In some embodiments of the present invention, the C6-C12 halogenated aromatic compound is selected from one or more of fluorobenzene, chlorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene and 1,2,3,4-tetrafluorobenzene.

[0025] In some embodiments of the present invention, the inducing agent is selected from one or more of 1,2-dichloroethane, 1,3-dichloropropane, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene and 1,4-difluorobenzene.

[0026] In some embodiments of the present invention, the lithium salt is selected from one or more of inorganic anion lithium salts and organic anion lithium salts.

[0027] In some embodiments of the present invention, the inorganic anion lithium salt is lithium hexafluorophosphate (LiPF6) and / or lithium tetrafluoroborate (LiBF4).

[0028] In some embodiments of the present invention, the organic anion lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium oxalate borate (LiBOB) and lithium difluorooxalate borate (LiDFOB), preferably lithium bis(fluorosulfonyl)imide (LiFSI) and / or lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0029] In some embodiments of the present invention, the concentration of lithium salt in the electrolyte is 0.33-1 mol / L; for example, it can be 0.33 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.55 mol / L, 0.6 mol / L, 0.65 mol / L, 0.7 mol / L, 0.75 mol / L, 0.8 mol / L, 0.85 mol / L, 0.9 mol / L, 0.95 mol / L or 1 mol / L, etc. Preferably, it is 0.66-1 mol / L.

[0030] In the present invention, when the concentration of lithium salt is kept within the above range, it helps to ensure that the lithium battery has a long cycle life and coulombic efficiency. If the concentration of lithium salt is too low, the proportion of anion decomposition is reduced, resulting in a decrease in the LiF content in SEI, which is likely to cause a decrease in the coulombic efficiency of the battery; if the concentration of lithium salt is too high, the lithium salt and the inducer will have a strong competitive relationship for solvent coordination, making the solvation structure unstable, which is likely to cause a decrease in the coulombic efficiency of the battery.

[0031] In a second aspect, the present invention provides a lithium battery comprising the electrolyte as described in the first aspect.

[0032] In some embodiments of the present invention, the positive electrode active material in the lithium battery includes one or more of lithium nickel cobalt manganese oxide, lithium nickel manganese oxide and lithium cobalt oxide, preferably lithium nickel cobalt manganese oxide.

[0033] In some embodiments of the present invention, the negative electrode active material in the lithium battery includes metallic lithium.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The electrolyte provided by the present invention realizes the dissolution of lithium salt in the solvent by utilizing the intermolecular interaction between the siloxane compound and the inducer. Due to the strong bond energy force between Si-O and the hyperconjugated interaction, the siloxane compound has fewer side reactions on the positive electrode side and higher antioxidant performance; at the same time, due to the strong anti-reduction ability of the siloxane compound and the weak solvation ability generated by the intermolecular mutual force between the siloxane compound and the inducer, a SEI film rich in LiF components generated by the decomposition of anions will be generated on the negative electrode side, which can effectively block the further reaction of the solvent with the lithium metal negative electrode. The electrolyte provided by the present invention has good stability to both the high-voltage positive electrode and the lithium metal negative electrode, has a wide electrochemical window, can be well matched with the high-voltage positive electrode material and the lithium metal negative electrode material, can be used in high-energy-density lithium metal batteries, and helps to improve the cycle life and coulomb efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1This is a graph showing the LSV test results of a Li / Al asymmetric battery using the electrolyte provided in Example 1;

[0037] Figure 2 This is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Example 1;

[0038] Figure 3 The graph is a test result of the cycle performance and coulombic efficiency of the NCM811 / Li battery using the electrolyte provided in Example 1;

[0039] Figure 4 This is a diagram showing the LSV test results of a Li / Al asymmetric battery using the electrolyte provided in Example 2;

[0040] Figure 5 The figure is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Example 2;

[0041] Figure 6 The graph is a test result of the cycle performance and coulombic efficiency of the NCM811 / Li battery using the electrolyte provided in Example 2;

[0042] Figure 7 This is a graph showing the LSV test results of a Li / Al asymmetric battery using the electrolyte provided in Example 3;

[0043] Figure 8 The figure is a graph showing the coulombic efficiency test result of a Li / Cu asymmetric battery using the electrolyte provided in Example 3;

[0044] Fig. 9 The graph is a test result of the cycle performance and coulombic efficiency of the NCM811 / Li battery using the electrolyte provided in Example 3;

[0045] Fig.10 This is a graph showing the LSV test results of a Li / Al asymmetric battery using the electrolyte provided in Example 4;

[0046] Fig.11 This is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Example 4;

[0047] Fig.12 The graph is a test result of the cycle performance and coulombic efficiency of the NCM811 / Li battery using the electrolyte provided in Example 4;

[0048] Fig.13 This is a graph showing the LSV test results of a Li / Al asymmetric battery using the electrolyte provided in Example 5;

[0049] Fig.14This is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Example 5;

[0050] Fig.15 The graph is a test result of the cycle performance and coulombic efficiency of the NCM811 / Li battery using the electrolyte provided in Example 5;

[0051] Fig.16 This is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Example 13;

[0052] Fig.17 This is a graph showing the LSV test results of a Li / Al asymmetric battery using the electrolyte provided in Comparative Example 3;

[0053] Fig.18 This is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Comparative Example 4. DETAILED DESCRIPTION

[0054] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementations. It should be understood by those skilled in the art that the specific implementations are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0055] In the embodiment of the present invention, the performance of the electrolyte is tested according to the following method:

[0056] (1) Electrochemical window

[0057] The electrochemical window of the electrolyte was tested using a Li / Al asymmetric battery, with a polyethylene (PE) diaphragm as the electrolyte load, an electrolyte injection volume of 75μL, a 2032 battery shell, and a sealing pressure of 1000kg. The test was performed using linear sweep voltammetry (LSV), with a test scan rate of 5mV / s and a scan voltage range of 3 to 5.5V.

[0058] (2) Coulomb efficiency

[0059] The coulombic efficiency of the electrolyte was tested using a Li / Cu asymmetric battery. The polyethylene (PE) diaphragm was used as the electrolyte load. The electrolyte injection volume was 75 μL. The battery shell was 2032 type and the sealing pressure was 1000 kg. The test current density was 0.5 mA / cm 2 The first cycle deposition amount is 5 mAh / cm 2 , then at 1 mAh / cm 2 The cycle was repeated 10 times, and finally all the lithium deposited on the Cu side was plated back to the lithium metal negative electrode side.

[0060] (3) Cycle performance

[0061] The cycle performance of the electrolyte was tested using a Li / NCM811 battery. A polyethylene (PE) diaphragm was used as the electrolyte load. The electrolyte injection volume was 75 μL. The battery shell was a 2032 model with a sealing pressure of 1000 kg. Preparation of the positive electrode sheet: NCM811 powder, PVDF binder, and carbon black were mixed evenly in N-methylpyrrolidone at a mass ratio of 96:2:2, and evenly coated on Al foil with a coater, and then placed in an 80°C oven for 12 hours to remove the solvent to obtain the positive electrode sheet for the experiment. The test voltage range was 2.7-4.4V, and the test rate was 0.2C charge and discharge.

[0062] Example 1

[0063] This embodiment provides an electrolyte, and the preparation method thereof is as follows:

[0064] 1 mL (0.0038 mol) of solvent 1,3-bis(trimethylsilyloxy)propane was thoroughly mixed with 2 mL (0.021 mol) of inducer fluorobenzene, and then 0.561 g of LiFSI was added, with a lithium salt concentration of 1 mol / L, and stirred until completely clear to obtain an electrolyte.

[0065] Figure 1 The figure is a linear sweep voltammetry (LSV) test result of a Li / Al asymmetric battery using the electrolyte provided in Example 1. Figure 1 It can be seen that in the scanning range of 3 to 5.5 V, the magnitude of the current is 10 -6 A, indicating that the electrolyte provided in Example 1 has good high-voltage resistance and can match high-voltage positive electrode materials.

[0066] Figure 2 The figure is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Example 1. Figure 2 It can be seen that its lithium metal coulombic efficiency reaches 99.6%.

[0067] Figure 3 The figure shows the cycle performance and coulombic efficiency test results of the NCM811 / Li battery using the electrolyte provided in Example 1. Figure 3 It can be seen that the capacity retention rate after 200 cycles is 100%, and the average Coulomb efficiency is above 99.9%.

[0068] Example 2

[0069] This embodiment provides an electrolyte, which differs from Embodiment 1 in that the inducing agent fluorobenzene is replaced by an equal volume (0.025 mol) of 1,2-dichloroethane.

[0070] Figure 4The figure is a linear sweep voltammetry (LSV) test result of a Li / Al asymmetric battery using the electrolyte provided in Example 2. Figure 4 It can be seen that in the scanning range of 3 to 5.5 V, the magnitude of the current is 10 -6 A, indicating that the electrolyte provided in Example 2 has good high-voltage resistance and can match high-voltage positive electrode materials.

[0071] Figure 5 The figure is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Example 2. Figure 5 It can be seen that its lithium metal coulombic efficiency reaches 99.4%.

[0072] Figure 6 The figure shows the cycle performance and coulombic efficiency test results of the NCM811 / Li battery using the electrolyte provided in Example 2. Figure 6 It can be seen that the capacity retention rate is 100% after 150 cycles, and the average Coulomb efficiency is above 99.8%.

[0073] Example 3

[0074] This embodiment provides an electrolyte, which is different from Embodiment 1 in that the inducing agent fluorobenzene is replaced by an equal volume (0.020 mol) of 1,2-difluorobenzene.

[0075] Figure 7 The figure is a linear sweep voltammetry (LSV) test result of a Li / Al asymmetric battery using the electrolyte provided in Example 3. Figure 7 It can be seen that in the scanning range of 3 to 5.5 V, the magnitude of the current is 10 -6 A, indicating that the electrolyte provided in Example 3 has good high-voltage resistance and can match high-voltage positive electrode materials.

[0076] Figure 8 The figure is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Example 3. Figure 8 It can be seen that its lithium metal coulombic efficiency reaches 99.2%.

[0077] Fig. 9 The figure shows the cycle performance and coulombic efficiency test results of the NCM811 / Li battery using the electrolyte provided in Example 3. Fig. 9 It can be seen that the capacity retention rate after 180 cycles is 97%, and the average Coulomb efficiency is above 99.8%.

[0078] Example 4

[0079] This embodiment provides an electrolyte, which differs from Embodiment 1 in that the solvent 1,3-bis(trimethylsilyloxy)propane is replaced with an equal volume (0.004 mol) of 1,2-bis(trimethylsilyloxy)ethane, and the lithium salt concentration is 0.66 mol / L.

[0080] Fig.10 The figure is a linear sweep voltammetry (LSV) test result of a Li / Al asymmetric battery using the electrolyte provided in Example 4. Fig.10 It can be seen that in the scanning range of 3 to 5.5 V, the magnitude of the current is 10 -6 A, indicating that the electrolyte provided in Example 4 has good high-voltage resistance and can match high-voltage positive electrode materials.

[0081] Fig.11 The figure is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Example 4. Fig.11 It can be seen that its lithium metal coulombic efficiency reaches 99.2%.

[0082] Fig.12 The figure shows the cycle performance and coulombic efficiency test results of the NCM811 / Li battery using the electrolyte provided in Example 4. Fig.12 It can be seen that the capacity retention rate after 200 cycles is 98%, and the average Coulomb efficiency is above 99.9%.

[0083] Example 5

[0084] This embodiment provides an electrolyte, which is different from Embodiment 4 in that the inducing agent fluorobenzene is replaced by an equal volume (0.0132 mol) of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0085] Fig.13 The figure is a linear sweep voltammetry (LSV) test result of a Li / Al asymmetric battery using the electrolyte provided in Example 5. Fig.13 It can be seen that in the scanning range of 3 to 5.5 V, the magnitude of the current is 10 -6 A, indicating that the electrolyte provided in Example 5 has good high-voltage resistance and can match high-voltage positive electrode materials.

[0086] Fig.14 The figure is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Example 5. Fig.14 It can be seen that its lithium metal coulombic efficiency reaches 99.5%.

[0087] Fig.15 The figure shows the cycle performance and coulombic efficiency test results of the NCM811 / Li battery using the electrolyte provided in Example 5. Fig.15 It can be seen that the capacity retention rate after 200 cycles is 99%, and the average Coulomb efficiency is above 99.9%.

[0088] Example 6

[0089] This embodiment provides an electrolyte, and the preparation method thereof is as follows:

[0090] 1 mL (0.003 mol) of solvent 1,2-bis(tert-butyldimethylsilyloxy)ethane was fully mixed with 0.4 mL (0.006 mol) of inducer dichloromethane, and then LiTFSI was added, with a lithium salt concentration of 1 mol / L, and stirred until completely clear to obtain an electrolyte.

[0091] The linear sweep voltammetry (LSV) test results of the Li / Al asymmetric battery using the electrolyte provided in Example 6 show that in the scanning range of 3 to 5.5 V, the current magnitude is between 10 -6 A, indicating that the electrolyte provided in Example 6 has good high-voltage resistance and can match high-voltage positive electrode materials.

[0092] The lithium metal coulombic efficiency of the Li / Cu asymmetric battery using the electrolyte provided in Example 6 reaches 98.5%.

[0093] The NCM811 / Li battery using the electrolyte provided in Example 6 has a capacity retention rate of 97% after 200 cycles, and an average coulombic efficiency of more than 99.5%.

[0094] Example 7

[0095] This embodiment provides an electrolyte, and the preparation method thereof is as follows:

[0096] 1 mL (0.0035 mol) of solvent bis[2-(trimethylsilyloxy)ethyl] ether and 1.05 mL (0.0105 mol) of inducer 2,2-dichloro-1,1,1-trifluoroethane were fully mixed, and then LiBOB was added, with a lithium salt concentration of 1 mol / L, and stirred until completely clear to obtain an electrolyte.

[0097] The linear sweep voltammetry (LSV) test results of the Li / Al asymmetric battery using the electrolyte provided in Example 7 show that in the scanning range of 3 to 5.5 V, the current magnitude is between 10 -6 A, indicating that the electrolyte provided in Example 7 has good high-voltage resistance and can match high-voltage positive electrode materials.

[0098] The lithium metal coulombic efficiency of the Li / Cu asymmetric battery using the electrolyte provided in Example 7 reaches 98.8%.

[0099] The NCM811 / Li battery using the electrolyte provided in Example 7 has a capacity retention rate of 97.5% after 200 cycles, and an average coulombic efficiency of more than 99.5%.

[0100] Example 8

[0101] This embodiment provides an electrolyte, and the preparation method thereof is as follows:

[0102] 1 mL (0.0036 mol) of solvent 1,2-bis(dimethylethoxysilyl)ethane and 2.1 mL (0.0144 mol) of inducing agent pentafluorobutane were fully mixed, and then LiDFOB was added, with a lithium salt concentration of 1 mol / L, and stirred until completely clear to obtain an electrolyte.

[0103] The linear sweep voltammetry (LSV) test results of the Li / Al asymmetric battery using the electrolyte provided in Example 8 show that in the scanning range of 3 to 5.5 V, the current magnitude is between 10 -6 A, indicating that the electrolyte provided in Example 8 has good high-voltage resistance and can match high-voltage positive electrode materials.

[0104] The lithium metal coulombic efficiency of the Li / Cu asymmetric battery using the electrolyte provided in Example 8 reaches 99%.

[0105] The NCM811 / Li battery using the electrolyte provided in Example 8 has a capacity retention rate of 98% after 200 cycles, and an average coulombic efficiency of more than 99.6%.

[0106] Example 9

[0107] This embodiment provides an electrolyte, and the preparation method thereof is as follows:

[0108] 1 mL (0.004 mol) of the solvent trimethylsilanol trisilyloxy glycolate was fully mixed with 2.54 mL (0.02 mol) of the inducer heptafluorocyclopentane, and then LiPF6 was added, with a lithium salt concentration of 1 mol / L, and stirred until completely clear to obtain an electrolyte.

[0109] The linear sweep voltammetry (LSV) test results of the Li / Al asymmetric battery using the electrolyte provided in Example 9 show that in the scanning range of 3 to 5.5 V, the current magnitude is between 10 -6 A, indicating that the electrolyte provided in Example 9 has good high-voltage resistance and can match high-voltage positive electrode materials.

[0110] The lithium metal coulombic efficiency of the Li / Cu asymmetric battery using the electrolyte provided in Example 9 reaches 98%.

[0111] The NCM811 / Li battery using the electrolyte provided in Example 9 has a capacity retention rate of 95% after 200 cycles, and an average coulombic efficiency of more than 99%.

[0112] Example 10

[0113] This embodiment provides an electrolyte, and the preparation method thereof is as follows:

[0114] 1 mL (0.0038 mol) of solvent 2,3-bis(trimethylsilyloxy)-1,3-butadiene was fully mixed with 2.35 mL (0.228 mol) of inducer 1,2,3-trifluorobenzene, and then LiBF4 was added with a lithium salt concentration of 1 mol / L, and stirred until completely clear to obtain an electrolyte.

[0115] The linear sweep voltammetry (LSV) test results of the Li / Al asymmetric battery using the electrolyte provided in Example 10 show that in the scanning range of 3 to 5.5 V, the current magnitude is between 10 -6 A, indicating that the electrolyte provided in Example 6 has good high-voltage resistance and can match high-voltage positive electrode materials.

[0116] The lithium metal coulombic efficiency of the Li / Cu asymmetric battery using the electrolyte provided in Example 10 reaches 98.6%.

[0117] The NCM811 / Li battery using the electrolyte provided in Example 10 has a capacity retention rate of 97% after 200 cycles, and an average coulombic efficiency of more than 99.6%.

[0118] Embodiment 11

[0119] This embodiment provides an electrolyte, and the preparation method thereof is as follows:

[0120] 1 mL (0.0038 mol) of solvent 1,3-bis(trimethylsilyloxy)propane was fully mixed with 0.5 mL (0.0052 mol) of inducer fluorobenzene, and then 0.187 g of LiFSI was added and stirred. It was found that the lithium salt could not be completely dissolved, and the mass of undissolved lithium salt was 0.15 g.

[0121] Example 12

[0122] This embodiment provides an electrolyte, and the preparation method thereof is as follows:

[0123] 1 mL (0.0038 mol) of solvent 1,3-bis(trimethylsilyloxy)propane was fully mixed with 2.5 mL (0.0266 mol) of inducer fluorobenzene, and then 0.187 g of LiFSI was added and stirred. It was found that the lithium salt could not be completely dissolved, and the mass of undissolved lithium salt was 0.1 g.

[0124] Example 13

[0125] This embodiment provides an electrolyte, and the preparation method thereof is as follows:

[0126] 1 mL (0.0038 mol) of solvent 1,3-bis(trimethylsilyloxy)propane was thoroughly mixed with 2 mL (0.021 mol) of inducer fluorobenzene, and then 0.187 g of LiFSI was added, with a lithium salt concentration of 0.33 mol / L, and stirred until completely clear to obtain an electrolyte.

[0127] Fig.16 The figure is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Example 13. Fig.13 It can be seen that its lithium metal coulombic efficiency is 98%, indicating that when the lithium salt concentration is low, the compatibility of the electrolyte with the lithium metal negative electrode decreases.

[0128] Comparative Example 1

[0129] In this comparative example, 0.187 g of LiFSI was added to 1 mL of 1,3-bis(trimethylsiloxy)propane solvent and stirred. As a result, it was found that the lithium salt could not be dissolved. This indicates that in the absence of an inducer, this type of siloxane solvent cannot dissociate the lithium salt, so the single-phase siloxane solvent is not suitable for lithium metal battery electrolyte.

[0130] Comparative Example 2

[0131] In this comparative example, 0.187 g of LiFSI was added to 1 mL of the inducer fluorobenzene and stirred, and it was found that the lithium salt could not be dissolved, indicating that the inducer itself could not be used as a solvent for the electrolyte.

[0132] Comparative Example 3

[0133] This comparative example provides an electrolyte, and its preparation method is as follows:

[0134] 0.187 g of LiFSI was added to 1 mL of ethylene glycol dimethyl ether with a lithium salt concentration of 1 mol / L, and stirred until completely clear to obtain an electrolyte.

[0135] Fig.17 The figure is a linear sweep voltammetry (LSV) test result of a Li / Al asymmetric battery using the electrolyte provided in Comparative Example 3. Fig.17 It can be seen that in the scanning range of 0 to 4.5 V, the magnitude of the current passing through is far more than 10 -6 A, indicating that the electrolyte provided in Comparative Example 3 does not have high voltage resistance and is therefore not compatible with high voltage positive electrode materials.

[0136] Comparative Example 4

[0137] This comparative example provides an electrolyte, and its preparation method is as follows:

[0138] 1 mL of ethylene carbonate and 1 mL of dimethyl carbonate were fully mixed, 0.3038 g of lithium hexafluorophosphate was added, and the lithium salt concentration was 1 mol / L. The mixture was stirred until completely clear to obtain an electrolyte.

[0139] Fig.18 The figure is a graph showing the coulombic efficiency test results of a Li / Cu asymmetric battery using the electrolyte provided in Comparative Example 4. Fig.18 It can be seen that its lithium metal coulombic efficiency is 84%, indicating that the carbonate-based electrolyte has poor compatibility with lithium metal and is not suitable for electrolytes used in lithium metal batteries.

[0140] It can be seen from the experimental results of the above embodiments that the electrolyte provided in Examples 1-10 of the present invention can dissolve lithium salts, has high compatibility with lithium metal negative electrodes (Li / Cu asymmetric battery CE>99%), has a wide electrochemical window of more than 5V, can be well matched with high-voltage positive electrode materials and lithium metal negative electrode materials, and the lithium battery using it has a longer cycle life.

[0141] Compared with Example 1, Example 11 has a lower ratio of inducer, and Example 12 has a higher ratio of inducer, which is not conducive to the interaction between the siloxane compound and the inducer, resulting in a decrease in its solubility in lithium salt. Compared with Example 1, Example 13 has a lower coulombic efficiency due to the lower concentration of added lithium salt.

[0142] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An electrolyte, characterized in that: The electrolyte comprises: a lithium salt, a solvent and an inducer; The solvent includes one or more of the siloxane compounds shown in Formula I; wherein X1 and X2 are each independently selected from one of C1-C4 alkyl groups, and R is selected from one of *-OLO-*; or, X1 and X2 are each independently selected from one of C1-C4 alkoxy groups, and R is selected from one of C2-C4 alkylene groups and *-OLO-*; L is selected from C2-C4 alkylene, *-Y1-O-Y2-*, Y1 and Y2 are each independently selected from one of C1-C2 alkylene groups, and Y3 is selected from one of C1-C3 alkylene groups; -* represents the attachment site of the group; The inducing agent is selected from one or more of C1-C5 halogenated alkanes, C1-C5 halogenated cycloalkanes, C2-C6 halogenated fatty ethers and C6-C12 halogenated aromatic compounds.

2. The electrolyte according to claim 1, characterized in that The molar ratio of the siloxane compound to the inducer is 1:(2-6).

3. The electrolyte according to claim 1 or 2, characterized in that The siloxane compound is selected from one or more of 1,2-bis(trimethylsiloxy)ethane, 1,3-bis(trimethylsiloxy)propane, 1,2-bis(tert-butyldimethylsiloxy)ethane, bis[2-(trimethylsiloxy)ethyl]ether, 1,2-bis(dimethylethoxysilyl)ethane, trimethylsilanol trisilyloxyglycolate and 2,3-bis(trimethylsiloxy)-1,3-butadiene, preferably 1,2-bis(trimethylsiloxy)ethane and / or 1,3-bis(trimethylsiloxy)propane.

4. The electrolyte according to any one of claims 1 to 3, characterized in that The halogen substituents in the C1-C5 halogenated alkane, C1-C5 halogenated cycloalkane, C2-C6 halogenated aliphatic ether and C6-C12 halogenated aromatic compound are fluorine and / or chlorine.

5. The electrolyte according to claim 4, characterized in that The C1-C5 halogenated alkane is selected from one or more of trichloromethane, dichloromethane, 1,2-dichloroethane, 1,3-dichloropropane, 1,1,2,2-tetrachloroethane, 2,2-dichloro-1,1,1-trifluoroethane and pentafluorobutane; The C1-C5 halogenated cycloalkane is heptafluorocyclopentane; The C2-C6 halogenated fatty ether is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and / or 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether; The C6-C12 halogenated aromatic compound is selected from one or more of fluorobenzene, chlorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene and 1,2,3,4-tetrafluorobenzene.

6. The electrolyte according to claim 5, characterized in that The inducing agent is selected from one or more of 1,2-dichloroethane, 1,3-dichloropropane, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene and 1,4-difluorobenzene.

7. The electrolyte according to any one of claims 1 to 6, characterized in that The lithium salt is selected from one or more of inorganic anion lithium salts and organic anion lithium salts; Wherein, the inorganic anion lithium salt is lithium hexafluorophosphate and / or lithium tetrafluoroborate; The organic anion lithium salt is selected from one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium oxalatoborate and lithium difluorooxalatoborate.

8. The electrolyte according to any one of claims 1 to 7, characterized in that: The concentration of the lithium salt in the electrolyte is 0.33-1 mol / L, preferably 0.66-1 mol / L.

9. A lithium battery, characterized in that: Comprising the electrolyte as described in any one of claims 1-8.

10. The lithium battery according to claim 9, characterized in that: The positive electrode active material in the lithium battery includes one or more of lithium nickel cobalt manganese oxide, lithium nickel manganese oxide and lithium cobalt oxide, preferably lithium nickel cobalt manganese oxide; Preferably, the negative electrode active material in the lithium battery includes metallic lithium.

Citation Information

Patent Citations

  • Secondary battery, battery pack, electric vehicle, power storage system, power tool, and electronic device

    CN104779381A

  • Nonaqueous electrolyte secondary battery and nonaqueous electrolyte solution

    CN106463772A

  • Overcharge-preventing lithium battery electrolyte for garden tool

    CN109980280A

  • Electrolyte for lithium ion battery, lithium ion battery, battery module, battery pack and device

    CN110767939A

  • Lithium ion battery electrolyte, preparation method and lithium ion battery

    CN111540954A

Cited By

  • Lithium-sulfur battery electrolyte, preparation method thereof and lithium-sulfur battery

    CN120824424A

  • Lithium battery electrolyte, lithium metal battery and cathode-free battery

    CN120878975A

  • Lithium battery electrolyte and lithium metal battery, negative electrode-free battery

    CN120878975B